An XAFS study of Cs adsorption by the precipitation bands of Mn–Fe-based Prussian blue analogues spontaneously formed in agarose gel. Issue 40 (7th October 2019) - Hayashi, Hisashi; Aoki, Saya; Takaishi, Mao; Sato, Yui; Abe, Hitoshi
Abstract : The adsorption of Cs + ions by the precipitation bands of a Mn–Fe based Prussian blue analogue that form spontaneously in agarose gel was investigated by XAFS spectroscopy coupled with SEM and XRF distribution analysis. Abstract : The adsorption of Cs + ions by the precipitation bands of a Mn–Fe based Prussian blue analogue (Mn–Fe PBA) that form spontaneously in agarose gel was investigated by X-ray absorption fine structure spectroscopy coupled with scanning electron microscopy (SEM) and X-ray fluorescence (XRF) distribution analysis. Two gel samples were prepared by contacting a gel containing 0.05 M [Fe(CN)6 ] 3− and 2.3 mass% agarose with a 0.50 M MnSO4 solution, into one of which a 0.10 M CsCl solution was introduced. The SEM images and the XRF intensity distributions reveal that Mn–Fe PBA forms cubic crystallites (approx. 3 × 3 × 3 μm in size) in the gels that trap Cs + ions with considerably high affinity. Cs L3 -edge and Mn K-edge X-ray absorption near-edge structure (XANES) spectra, which were analyzed with the aid of FEFF simulations, strongly suggest that Cs adsorption occurs at relatively large defect sites close to the sub-cube faces in the PBA. This suggestion is supported by Cs L3 -edge extended X-ray absorption fine structure spectroscopy, which suggested that the first and second coordination shells around the Cs + ions are at a Cs–O distance of 0.35 ± 0.02 nm and a Cs–N distance of 0.43 ± 0.01 nm, respectively, with coordination numbers of 1.5 ± 0.5 and 3.0 ± 0.5. The Mn K-edge XANES data also suggest that H2 O molecules, which initially occupy many cubic centers in the Mn–Fe PBAs, are mostly displaced during Cs adsorption. These findings provide valuable insight toward fully understanding Cs adsorption by Mn–Fe PBA.